(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the translation features of language units used in economic texts from English into Uzbek. Particular attention is paid to economic terms, terminological word combinations, and common lexical units that acquire specialized meanings in economic discourse. The paper analyzes the main difficulties arising in the translation of such units and discusses the ways of rendering them adequately. It also highlights the use of equivalence, adequacy, functional correspondence, calque, descriptive translation, and contextual substitution on the basis of practical examples. The study argues that in translating economic texts it is necessary to consider not only the dictionary meaning of language units, but also their terminological, stylistic, and pragmatic characteristics.